Educational leadership and transformation in Higher education in Colombia: Guidelines for Competency-based Microcurricular Design - Grisales Herrera, Beatriz Eugenia (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This article aims to provide guidelines for microcurricular design in the context of higher education in colombia, in response to the need to adapt to global changes and the demands of an evolving job market, based on the experience of a university in Cali, Colombia. these microcurricular design guidelines focus on identifying the learning processes that students must develop to achieve the objectives and learning outcomes within the development of a competency-based educational model. it highlights the importance of implementing flexible and innovative curricula that prioritize the development of practical skills, which requires the inclusion of learning outcomes as guidelines for what is expected in learning. educational leadership should guide this transformation, inviting consideration to ensure the quality of learning from a broader perspective that includes not only curricular quality conditions at the macro and meso-curricular levels of educational institutions but also extends to the micro-curriculum.